Controle de qualidade da droga vegetal e avaliação da atividade hipolipidêmica in vivo do extrato aquoso dos frutos de passiflora Cincinnata mast. (Passifloraceae) - Leal, Ana Ediléia Barbosa Pereira (2022)
The present study was divided into two chapters. The first chapter proposed to investigate patents related to biological activities of the genus Passiflora, where was observed the great potential of several parts of different species, to obtain phytoproducts. The second chapter proposed to obtain fruit peel extracts of P. cincinnata and to evaluate its hypolipidemic activity in vivo, as important steps for the development of herbal medicines. Thus, were performed physicochemical tests with the vegetable drug, according to Brazilian Pharmacopoeia, analysis of chemical constituents present in extracts, through high-performance liquid chromatography (HPLC-DAD), as well as, evaluation of acute toxicity, hypolipidemic activity of the extract (administered orally: 100 and 200 mg/kg), in induced hyperlipidemic mice, and investigation of the possible mechanism of action, through molecular dynamics simulations. The physicochemical assays were within the pharmacopoeial standards. The presence of the vitexin, orientin and isoorientin was confirmed by HPLC-DAD. No clinical signs of toxicity were observed in the evaluated animals. The hypolipidemic analysis presented a reduction in total cholesterol levels (TC) and an increase in high-density lipoprotein (HDL-c), statistically significant (p < 0.05), when compared to control only induced, while triglycerides indices (TG) did not show a significant response. The analysis of molecular docking showed that the compounds in general showed stability in practically the entire simulation, mainly the vitexin, when associated with the LCAT enzyme, demonstrating that the evaluated extract has lipid-lowering activity, possibly due to the presence of the identified bioactive compounds.